Characteristics and radiation tolerance of a double-sided microstrip detector with polysilicon biasing resistors - de Haas, A.P.; Kuijer, P.; Kulibaba, V.I.; Maslov, N.I.; Perevertailo, V.L.; Ovchinnik, V.D.; Potin, S.M.; Starodubtsev, A.F. (Вопросы атомной науки и техники, 2000)
The characteristics and radiation tolerance of a double-sided microstrip detector (DSMD) were studied, and the suitability of the detector to the ALICE experiment requirements was analyzed. The sensitive area of the silicon microstrip detector measures 40x75 mm. The DSMD consists of 750 registering strips on each side. The strip pitch is 100 mm and the strip length is 40 mm. Strips of the p+-side were oriented parallel to the side edge, the n+-strips were placed at 30 mrad stereo angle with respect to p+-strips and were separated by a common p+-stop structure. Both p+- and n+-strips are biased by integrated polysilicon resistors with a resistance no less than 10 MOhm. The data readout is realized with use of 120 pF coupling capacitors. The radiation tolerance of the microstrip detector was studied using 20 MeV electrons. The leakage current increases from 2 up to 5 nA per one strip and the interstrip resistance decreases from 43 down to 30 GOhm after 10 krad irradiation dose. The other DSMD features remain unchanged under irradiation. To evaluate the detector efficiency, the yield of good coupling capacitors and biasing resistors, as well as strip leakage currents, interstrip resistance and interstrip capacitance were studied. Based on the data obtained, the number of defective strips is found not to exceed 3%; this provides the required detector efficiency of about 97%.